النسخ بين النظرية والتطبيق في سورة البقرة:دراسة مقارنة بين التهانوي والقنوجي: Abrogation Between Theory and Practice in Surah Al-Baqarah: A Comparative Study of al-Thānwī and al-Qannūjī - Ghazi, Hafsa (Al Basirah, 2025)
Background of the study: Abrogation remained an important concept in Qur’anic studies, with implications for legal interpretation and exegesis. Despite its importance, most previous studies have focused either on its theoretical framework or on practical examples, leaving a gap in combined analyses of both dimensions. Objectives: This study aims to explore both the theoretical and practical dimensions of abrogation (Al-Naskh) in the Holy Qur’an. It first defines abrogation and outlines the conditions established by scholars, then examines the extent to which these conditions were applied by two prominent exegetes of the Indian subcontinent, Ashraf ʿAlī Thānawī and Nawwāb Ṣiddīq Ḥasan Khān Qannūjī. The study further offers a comparative analysis of their interpretations, limited to Surah al-Baqarah. Methodology: The research employs the inductive method to collect conditions of abrogation from available sources, the analytical method to assess their application in the works of the two exegetes, and the comparative method to highlight similarities and differences between them. Findings: The study shows that scholars of the subcontinent devoted considerable attention to the question of abrogation and generally implemented the conditions established by earlier scholars. Nevertheless, some divergences were identified, reflecting differing views on the necessity of certain conditions. Originality: Unlike previous studies that have tended to focus exclusively on either the theoretical or the practical dimensions of abrogation, this study integrates both perspectives within a single analytical framework. It further contributes to the field by presenting a systematic comparative analysis of two influential exegetes from the Indian subcontinent. By doing so, the study offers a deeper methodological insight into the application of Naskh in Qur’anic interpretation and helps refine contemporary scholarly understanding of its scope and function. Conflict of Interest: The authors declare that there are no conflicts of interest related to the research, authorship, and/or publication of this article, and that the data presented have not been fabricated or falsified. Funding: This research did not receive any specific grant or financial support from public, commercial, or not-for profit funding agencies. Participant Consent: The authors confirm that Informed consent was obtained from all participants, and confidentiality was duly maintained. Data Fabrication/Falsification Statement: The author(s) declare that no data have been fabricated, falsified, or manipulated in this study. Copyright: Author(s) retains the Copyright of this article.